2015
DOI: 10.1002/2015gl065602
|View full text |Cite
|
Sign up to set email alerts
|

Short‐tailed temperature distributions over North America and implications for future changes in extremes

Abstract: Some regions of North America exhibit nonnormal temperature distributions. Shorter‐than‐Gaussian warm tails are a special subset of these cases, with potentially meaningful implications for future changes in extreme warm temperatures under anthropogenic global warming. Locations exhibiting shorter‐than‐Gaussian warm tails would experience a greater increase in extreme warm temperature exceedances than a location with a Gaussian or long warm‐side tail under a simple uniform warm shift in the distribution. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…The decreased variability noted above also occurred in the Northeast for the WGN and WH simulations, but the background warming for this region caused the median to shift enough that the historical 95th percentile still occurred close the 50th percentile. This result is in good agreement with Loikith and Neelin () where they concluded that shorter‐than‐Guassian high‐side tails have the potential to greatly increase in the frequency of extreme values if the shift in the PDF mean is large enough. For the Midwest and Northeast, the WGN and WH simulations experience a shorter‐than‐Guassian high‐side tail, but the background warming in the mean is large enough in the Northeast to still yielded greater increases in the TMAX extremes.…”
Section: Summer Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The decreased variability noted above also occurred in the Northeast for the WGN and WH simulations, but the background warming for this region caused the median to shift enough that the historical 95th percentile still occurred close the 50th percentile. This result is in good agreement with Loikith and Neelin () where they concluded that shorter‐than‐Guassian high‐side tails have the potential to greatly increase in the frequency of extreme values if the shift in the PDF mean is large enough. For the Midwest and Northeast, the WGN and WH simulations experience a shorter‐than‐Guassian high‐side tail, but the background warming in the mean is large enough in the Northeast to still yielded greater increases in the TMAX extremes.…”
Section: Summer Resultssupporting
confidence: 90%
“…This is most evident in Northwest (Figure c) where the variability decreases by 15%–38% (17%–28%) for all five simulations when measuring the interquartile range for 2085–2094 under both scenarios (R8Y4) scenario. The proximately to the Pacific Ocean is likely a moderating factor in these PDF curves as the cool ocean water likely limit large increases to the warm side during the winter months (Loikith & Neelin, ). The Midwest experience similar morphology change in the PDF curves with a 16–29% decrease in IQR change under R8Y8.…”
Section: Winter Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work with this model will include land‐sea contrast and a simple treatment of vertical motion to enable comparisons with Northern Hemisphere data. Nevertheless, the results of this simple model that changes to both the variance and the skewness are inherent to global warming suggest caution in applying Gaussian statistics for predicting future extremes (e.g., Loikith & Neelin, ).…”
Section: Discussionmentioning
confidence: 99%
“…To understand long‐tail and short‐tail temperature distributions (e.g., Loikith & Neelin, ), we solve the advection‐diffusion equation on the sphere using the pseudo‐spectral method for temperature θ , with Newtonian relaxation to a prescribed equilibrium temperature profile: ∂θ∂t=boldv·θθθeqτκ8θ, where κ is the hyper‐diffusion coefficient that results in a 0.1 day damping timescale on the smallest resolved spherical harmonic and τ is the thermal relaxation timescale. The model is run at T42 resolution.…”
Section: Advection‐diffusion Model Of Temperaturementioning
confidence: 99%